Green synthesis of gold nanoparticles by using Ferula persica Willd. gum essential oil: production, characterization and in vitro anti-cancer effects. (21st April 2020) - Hosseinzadeh, Neda; Shomali, Tahoora; Hosseinzadeh, Saeid; Raouf Fard, Fatemeh; Pourmontaseri, Maryam; Fazeli, Mehdi
Abstract: Objectives: Synthesizing and characterization of gold nanoparticles (Au NPs) by Ferula persica gum essential oil and investigating in vitro anti-cancer effects. Methods: Characterization of NPs was performed. Cytotoxicity and apoptosis were determined on cancerous CT26 and non-cancerous Vero cells using MTT assay and acridine orange/ethidium bromide (AO/EB) staining, respectively. Clonogenic assay was also performed. Key findings: The absorption peak in UV-visible spectroscopy was at 530 nm. In TEM image, Au NPs were spherical in shape with average size of 37.05 nm (78.6 nm in DLS analysis). Comparison of the FTIR spectrum of the Au NPs with the essential oil revealed the presence of compounds responsible for reducing and capping the gold ions. XRD pattern showed metal crystal structure. Au NPs exerted dose-dependent cytotoxicity with IC50 values of 0.0024 and 0.0307 mg/ml against CT26 and Vero cell lines, respectively. Au NPs induced apoptosis on both cell lines with statistically more intense effect on CT26 cells ( P < 0.0001). Colony formation of CT26 and Vero cells was also inhibited in comparison to untreated cells ( P < 0.05). Conclusions: Ferula persica gum can be successfully used for green production of Au NPs. Au NPs show in vitro anti-cancer activity including cytotoxic, apoptotic and antiproliferative effects.